Applying MDP Approaches For Estimating Outcome of Interaction in Collaborative Human-Computer Settings - Kamar, Ece; Grosz, Barbara J. (In Proceedings of Workshop on Multi-agent Sequential Decision Making in Uncertain Domains (MSDM) 2007, 2007)
This paper investigates the problem of determining when a computer agent should interrupt a person with whom it is working collaboratively as part of a distributed, multi-agent team, which is operating in environments in which conditions may be rapidly changing, actions occur at a fast pace, and decisions must be made within tightly constrained time frames. An interruption would enable the agent to obtain information useful for performing its role in the team task, but the person will incur a cost in responding. The paper presents a formalization of interruptions as multi-agent decision making. It defines a novel, efficient approximation method that decouples the multi-agent decision model into separate MDPs, thereby overcoming the complexity of finding optimal solutions of the Dec-POMDP model. For singleshot situations, the separate outcomes can be combined to give an exact value for the interruption. In more general settings, the closeness of the approximation to the optimal solution depends on the structure of the problem. The paper describes domain specific heuristic functions that improve the efficiency of the approximation further for a specific application.